Estudo do tegumento de cabras da raça saanen e seus mestiços com boer - De Oliveira Aiura, Auriclécia Lopes; Aiura, Felipe Shindy; Santos, Laize Vieira; Santana, Claudia Juliane Lopes; Da Silva, Roberto Gomes [UNESP]; Machado, Márcia Rita Fernandes [UNESP] (My University, 2014)
The study aimed to evaluate Saanen goats and their crossbred Boer through the structures of tegument: sweat ducts, sebaceous glands, hair follicles and epidermal thickness as their thermoregulatory characteristics. Samples of tegument of genetic groups Saanen and Saanen x Boer were collected of the cervical, thoracic and gluteal regions for the preparation of histological slides. Thus the following measurements were obtained: epidermal thickness (μm); hair follicles per area (2,281,700 μm2); area (μm 2), perimeter (μm) and quantity per area (2,281,700 μm 2) of the sweat ducts and sebaceous glands. The experimental design was completely randomized in 2x3 factorial (two genetic groups and three regions of tegument collection). Crossbred animal had greater number of hair follicles, which promotes greater protection factor to solar radiation, and the gluteal region responsible by largest number of follicles.
Tegument study of saanen goats and their crossbred boer
Keywords: Epidermis thickness; Hair follicles; Sebaceous glands; Sweat ducts